Building a Civilising Matrix as a Way to Good Living - Calderón Vélez, Milton (2018)
Two civilizational models configure the thinking and cultural practices in the Latin Americas: the modern Western and the ancient contemporary, both in permanent construction. Against this, are required inter civilizational dialogue processes that are directed towards the so-called trans-modernity and culminate in the approaching to the “Wonder Living” paradigm and South epistemology. This route has to pass through the recognition of own knowledge and ideas, the struggle for common goals, planetary gaze, and science that points to endogenous development and complexity.